Rapid weight loss can increase the risk of acute kidney injury in wrestlers - Natasa Zenic; Patrik Drid; Attilio Carraro; Tatjana Trivic; Roberto Roklicer; Toni Modric; Aleksandra Milovancev; Mirka Lukic-Sarkanovic; Nemanja Maksimovic; Antonino Bianco (BMJ Open Sport & Exercise Medicine, 2023)
Objective Restrictive diets, forced starvation or voluntary weight loss are attracting more and more attention from scientists. Overall trends show that about 80% of combat sports athletes use specific methods of reducing body mass. Rapid weight loss could be a risk factor for kidney-related adverse outcomes. This study aimed to examine the impact of high-intensity specific training combined with rapid weight loss in the first and without rapid weight loss in the second phases on body composition and biochemical markers of kidney function.Methods The study was conducted on 12 male wrestlers. Kidney function markers were measured, including blood urea nitrogen, serum creatinine, uric acid and serum Cystatin-C. Alterations in analysed markers were noted in both phases of the research.Results According to the data, a significant increase was noted in blood urea nitrogen (p=0.002), uric acid (p=0.000) and serum creatinine (p=0.006) during the first phase in comparison with the second phase. The levels of serum Cystatin-C were slightly elevated after both phases compared with the initial measurement.Conclusion It is evident that high-intensity specific training combined with rapid weight loss significantly affects the increase in kidney function markers compared with identical training without rapid weight loss. The findings in this study suggest that rapid body mass reduction is associated with an increased risk of acute kidney injury in wrestlers.